PENINGKATAN SKILL MASYARAKAT DESA WISATA RINDU HATI DALAM MEMANFAATKAN ENERGI MATAHARI MENJADI ENERGI LISTRIK MENGGUNAKAN PANEL SURYA - Elfi Yuliza; Riska Ekawita; Rida Samdara (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Rindu Hati Village, located in the Central Regency of Bengkulu, is one of the tourist villages in Bengkulu Province. This village has various natural tourist potentials such as waterfalls, expanses of plantations and rice fields, camping grounds, rafting, etc. However, access to electricity for this area is still very limited. It can be seen in the unavailability of streetlights on site, very limited lighting in tourist areas, etc. In fact, this area receives sunlight all day long throughout the year which can be applied for lighting using solar panels. The limited knowledge and skills of the community regarding the various variations of solar panel technology and the installation process are the reasons why this technology was not used. Therefore, in this service activity, various solar panel technologies were explained and training on their use, especially for tourism awareness groups in Rindu Hati village. This activity is divided into five stages, the first stage is exposure to the use of solar panel technology, followed by training on the installation of various forms of solar panels and the last stage installation solar panels for the lighting of the campsite. In addition, before and after the presentation and training, a questionnaire was handed out which aims to determine the public's knowledge of solar panel technology. The results of the questionnaire show that the public is already familiar with solar panels for producing electrical energy, but limitation in the form and variation. During the implementation of the activity, the community showed interest in using solar panels in their homes. In addition, this activity increases the knowledge and skills of the community in the use of solar energy by using solar panels for various purposes such as lighting and electricity for electronic devices in the household